Profil Gratitude Mahasiswa - Fajar Ilham; Nandang Rusmana; Nandang Budiman (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2019)
This study aims to determine the condition of gratitude for new students in the geography education study program at Indonesia University of Education. This research is a quantitative research with descriptive method. The instrument used in this study is the scale of gratitude. The subjects in this study were 78 new students in the 2018/2019 geography education study program. Data analysis in this study used descriptive statistics with percentage techniques. The results showed that 14,1% of students had high gratitude, 47,4% of students had medium gratitude, and 38,5% of students had low gratitude. The results of this study were useful for lecturer